Implementation of Islamic Religious Education Curriculum Based on the 2013 Curriculum at Unggulan Permatajingga Elementary School, Malang - Imam Taqyudin; M. Jamal Abdul Nasir (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Permatajingga Superior Elementary School Malang is a public school that implements the 2013 curriculum. Even though as a public school the leadership of Permatajingga Superior Elementary School has the hope that its students have Islamic character, and Islamic religious abilities that are weightier when compared to equivalent public schools. In order to realize this hope, the leadership of Permatajingga Primary School seeks to optimize extracurricular activities and religious habituation in schools. The purpose of this study was to examine the planning, implementation, and evaluation of the 2013 curriculum-based Islamic Education curriculum which focused on extracurricular and religious habituation. This research is qualitative descriptive research. Collecting data using interviews, observation, and documentation techniques. Primary data sources are the Principal, Deputy Head of Curriculum, and Islamic Education Teachers. The data were analyzed using data analysis techniques, data reduction, and data presentation, as well as drawing conclusions. The results of the assessment show that the planning of extracurricular activities and religious habituation is carried out at the beginning of the semester which includes the objectives of the activity, the preparation of programs and schedules, as well as an analysis of the needs of students' talents and interests. The implementation of extracurricular activities and religious habituation goes according to the plans and programs that have been prepared. Evaluation is carried out every six months involving all educators and school education. From the evaluation it was found that the school's expected goals have been achieved but there are still obstacles such as limited infrastructure and student discipline.